2020
DOI: 10.31149/ijie.v3i10.693
|View full text |Cite
|
Sign up to set email alerts
|

Competencies of Librarians as a Factor Affecting Information, Service Delivery in Selected University Libraries in Delta State, Nigeria

Abstract: This study investigated the competencies of librarians as a factor affecting information service delivery in Delta state university (DELSU) library and Federal university of petroleum resources (FUPRE) library. The main objective of the study was to determine the extent to which information and competencies of librarians in DELSU and FUPRE affect their information service delivery. The instrument used for data collection was the questionnaire. A descriptive survey design was used in this study. A total of 61 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…The result of the study also agrees with the study by Ubogu (2021), who identify the following challenges associated with capacity-building practices for effective service delivery: non-availability of information materials, inaccessibility of reading materials, lack of infrastructure, lack of competency and adaptation, lack of technology literacy, inadequate power supply and poor funding. The challenge of finance observed in this study is in line with the study of Idhalama et al . (2021) who observed that the state of financial resources necessary for positive intervention in the learning capacity-building initiatives in the profession is grossly inadequate.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The result of the study also agrees with the study by Ubogu (2021), who identify the following challenges associated with capacity-building practices for effective service delivery: non-availability of information materials, inaccessibility of reading materials, lack of infrastructure, lack of competency and adaptation, lack of technology literacy, inadequate power supply and poor funding. The challenge of finance observed in this study is in line with the study of Idhalama et al . (2021) who observed that the state of financial resources necessary for positive intervention in the learning capacity-building initiatives in the profession is grossly inadequate.…”
Section: Resultssupporting
confidence: 92%
“…Therefore, inadequate fund has always been a primary hindrance to capacity building for effective service delivery in libraries. Accordingly, Idhalama et al (2021) observe that the challenge of building and sustaining adequate library and information services capacity in federal university libraries in Nigeria constitutes a serious problem. They further argued that the state of financial resources necessary for positive intervention in the capacity-building programs in the profession is greatly inadequate.…”
Section: Challenges Associated With Learning Capacity-building Practi...mentioning
confidence: 99%
See 1 more Smart Citation
“…A pyramid model can be established. Under the stratification of the pyramid, a hierarchical decision-making organization can be realized through several specific objectives to help the decisionmaking science of student management [10]. Qiao and others believe that at present, most colleges and universities have completed information construction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The College library, which has for quite some time been perceived as "the heart" of each and every scholastic organization, is one spot where the advantages of Information & Communication Technology (ICT) are immense. Idhalama (2020) (Abbas & Siddique, 2020).…”
Section: Introductionmentioning
confidence: 99%